1969
DOI: 10.1530/jrf.0.0200279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progesterone on Induced Ovulation in Immature Rats

Abstract: Summary. Female rats treated with 3 i.u. PMSG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1971
1971
1992
1992

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…In addition, progesterone has been shown to increase plasma LH (Nallor, Antunes-Rodrigues & McCann, 1966;Caligaris et al 1968) and to increase pituitary LH (Labhsetwar, 1969). Similar observations on stimulation (McCormack & Meyer, 1963;Zarrow & Hurlbut, 1967;Ying & Meyer, 1969) and inhibition (Zarrow & Hurlbut, 1967;Ying & Meyer, 1969) of ovulation by progesterone have been reported in the PMS-treated immature rat. Thus the findings indicate that the action of progesterone on ovulation is biphasic in the immature rat as well as in the mature rat.…”
Section: Treatment With Pregnant Mare Serumsupporting
confidence: 74%
“…In addition, progesterone has been shown to increase plasma LH (Nallor, Antunes-Rodrigues & McCann, 1966;Caligaris et al 1968) and to increase pituitary LH (Labhsetwar, 1969). Similar observations on stimulation (McCormack & Meyer, 1963;Zarrow & Hurlbut, 1967;Ying & Meyer, 1969) and inhibition (Zarrow & Hurlbut, 1967;Ying & Meyer, 1969) of ovulation by progesterone have been reported in the PMS-treated immature rat. Thus the findings indicate that the action of progesterone on ovulation is biphasic in the immature rat as well as in the mature rat.…”
Section: Treatment With Pregnant Mare Serumsupporting
confidence: 74%
“…Proges¬ terone administration can advance ovulation by 24 h in PMSG-treated rats (Ying & Meyer, 1969;Zarrow & Gallo, 1969). The serum progesterone response to PMSG was reduced in our study by prior cortisolacetate treatment and this may explain why fewer of these animals than controls had ovulated within 48 h of PMSG injection.…”
Section: Discussionmentioning
confidence: 46%
“…In hamsters, however, Greenwald (1971) showed that simultan¬ eous injection of progesterone with lower doses of PB (which did not cause behavioural depression) restored ovulation in many of the treated animals. The effects produced by PB and progesterone are therefore to be interpreted with caution as the time and dose of injection in relation to the stage of the oestrous cycle and lighting regimen, and the presence of other steroids can all influence the results (Strauss, 1964;Ying & Meyer, 1969b;Harris & Naftolin, 1970). Although the present study deals with the effects of progestational steroids, the profound influence of oestrogen in the sequence of events leading to ovulation is known to be equally important (Neill, Freeman & Tillson, 1971).…”
Section: Discussionmentioning
confidence: 99%